Unrecognized Pseudohypoparathyroidism Type 1A as a Cause of Hypocalcemia and Seizures in a 64-Year-Old Woman. (9th January 2019) - Del Monte, Patrizia; Cuttica, Carla Micaela; Marugo, Alessandro; Foppiani, Luca; Audenino, Daniela; Godowicz, Tomasz Tadeusz; Elli, Francesca Marta; Mantovani, Giovanna; Di Maria, Emilio
Abstract : Pseudohypoparathyroidism type 1A (PHP1A) is usually diagnosed in childhood or early adulthood. We describe the case of a 64-year-old woman admitted to the Neurological Unit for recurrent episodes of loss of consciousness and seizures. Glycemia and ECG were normal, while hypocalcemia was noted. Clinical history revealed carpo-pedal spasm since the age of 30 years, cognitive impairment, hypothyroidism since early adulthood, and menopause at 30 years. She was taking oral calcium and cholecalciferol for chronic hypocalcemia. Physical features suggested Albright's osteodystrophy. Blood calcium was confirmed low, with increased parathyroid hormone, moderate 25OH-vitamin D deficiency, and normal creatinine. Brain CT scan revealed calcifications of the basal ganglia, cortical and subcortical white matter, and cerebellum. Therapy was switched to oral calcitriol, with normalization of calcium levels; levetiracetam was started and no further seizures occurred. The clinical diagnosis of PHP1A was confirmed by molecular analysis, which demonstrated the heterozygous c.568_571del mutation of the GNAS gene. Our report illustrates the natural history of a patient with PHP1A, which went undiagnosed until the age of 64 years, with multi-hormonal resistance and clinical sequelae evolving throughout life, and underlines the importance of diagnosing this rare disease, which has a great impact on patients and their family life.